2021
DOI: 10.1038/s41598-021-92104-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of coarctation degrees on wall shear stress indices

Abstract: Coarctation of the aorta (CoA) is a congenital tightening of the proximal descending aorta. Flow quantification can be immensely valuable for an early and accurate diagnosis. However, there is a lack of appropriate diagnostic approaches for a variety of cardiovascular diseases, such as CoA. An accurate understanding of the disease depends on measurements of the global haemodynamics (criteria for heart function) and also the local haemodynamics (detailed data on the dynamics of blood flow). Playing a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…The variation of OSI in moderate and regular models turns into more stable, suggesting a better mechanical condition for the aortic endothelial cells. As reported by previous research 6 , 29 , 57 , an invaluable part of WSS indicators is that if an area exposes to a high OSI and low TAWSS, there is a high risk of rupture, calcification, or wall thickening. High OSI values in distal FL with low TAWSS (around DA) can potentially lead to high-risk complications.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The variation of OSI in moderate and regular models turns into more stable, suggesting a better mechanical condition for the aortic endothelial cells. As reported by previous research 6 , 29 , 57 , an invaluable part of WSS indicators is that if an area exposes to a high OSI and low TAWSS, there is a high risk of rupture, calcification, or wall thickening. High OSI values in distal FL with low TAWSS (around DA) can potentially lead to high-risk complications.…”
Section: Discussionmentioning
confidence: 83%
“…In recent years, several studies have reported the importance of personalised computational fluid dynamics (CFD) methods along with imaging techniques to develop diagnosis and controlling approaches of aortic disease, in order to customize patient-specific treatment outcomes 23 29 . Some studies have shown the importance of the combination of particle image velocimetry and CFD simulations in type-B AD in pre-procedural planning, clinical decision support, and CFD models validation 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Future work includes developing a large in-vitro database using our setup for resolving issues related to usually small-sized in-vivo databases in order to facilitate specific hemodynamics-based big-data studies [4345]. In addition, the setup can be used to simulate more complicated diseases, e.g., myocardial infarction, hemorrhagic shock, or aortic coarctation, where several physiological responses need to be simulated (i.e., changing our setup based on the main pathophysiology/abnormalities of the corresponding disease condition) [30, 46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…Other future works include developing a large in-vitro database using our setup for resolving issues related to usually small-sized in-vivo databases to facilitate specific hemodynamicsbased big-data studies [58][59][60][61][62] (more details were provided in Section 4.). In addition, as mentioned in Section 4, the setup can be used to simulate more complicated diseases, e.g., myocardial infarction, hemorrhagic shock, or aortic coarctation/dissection, where several physiological responses need to be simulated (i.e., changing our setup based on the main pathophysiology/abnormalities of the corresponding disease condition) [32,63].…”
Section: Plos Onementioning
confidence: 99%